MICA and NKG2D: Is There an Impact on Kidney Transplant Outcome? - Risti, Matilde; Bicalho, Maria da Graça (Frontiers in Immunology, 2017)
This paper aims to present an overview of MICA and NKG2D genetic and functional interactions and their impact on kidney transplant outcome. Organ transplantation has gone from what can accurately be called a ‘‘clinical experiment’’ to a routine and reliable practice, which has proven to be clinically relevant, life-saving and cost effective when compared with non-transplantation management strategies of both chronic and acute end stage organ failures. The kidney is the most frequently transplanted organ in the world (transplant-observatory). The two treatment options for end-stage renal disease (ESRD) are dialysis and/or transplantation. Compared with dialysis, transplantation is associated with significant improvements in quality of life and overall longevity. A strong relationship exists between allograft loss and Human Leukocyte Antigens (HLA) antibodies. HLA antibodies are not the only factor involved in graft loss, as multiple studies have shown that non-HLA antigens are also involved, even when a patient has a good HLA matche and receives standard immunosuppressive therapy. A deeper understanding of other biomarkers is therefore important, as it is likely to lead to better monitoring (and consequent success) of organ transplants. The objective is to fill the void left by extensive reviews that don’t often dive this deep into the importance of MICA and NKG2D in allograft acceptance and their partnership in the immune response. There are few papers that explore the relationship between these two protagonists when it comes to kidney transplantation. This is especially true for the role of NKG2D in kidney transplantation. These reasons give a special importance to this review, which aims to be a helpful tool in the hands of researchers in this field.